The CCN Family Proteins: Modulators of Bone Development and Novel Targets in Bone-Associated Tumors. (14th January 2014) - Chen, Po-Chun; Cheng, Hsu-Chen; Yang, Shun-Fa; Lin, Chiao-Wen; Tang, Chih-Hsin
Abstract : The CCN family of proteins is composed of six extracellular matrix-associated proteins that play crucial roles in skeletal development, wound healing, fibrosis, and cancer. Members of the CCN family share four conserved cysteine-rich modular domains that trigger signal transduction in cell adhesion, migration, proliferation, differentiation, and survival through direct binding to specific integrin receptors and heparan sulfate proteoglycans. In the present review, we discuss the roles of the CCN family proteins in regulating resident cells of the bone microenvironment. In vertebrate development, the CCN family plays a critical role in osteo/chondrogenesis and vasculo/angiogenesis. These effects are regulated through signaling via integrins, bone morphogenetic protein, vascular endothelial growth factor, Wnt, and Notch via direct binding to CCN family proteins. Due to the important roles of CCN family proteins in skeletal development, abnormal expression of CCN proteins is related to the tumorigenesis of primary bone tumors such as osteosarcoma, Ewing sarcoma, and chondrosarcoma. Additionally, emerging studies have suggested that CCN proteins may affect progression of secondary metastatic bone tumors by moderating the bone microenvironment. CCN proteins could therefore serve as potential therapeutic targets for drug development against primary and metastatic bone tumors.